(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2026)
The aim of the research was to investigate the attitudes of teachers in the Karak Education Directorate towards the usage of electronic educational games in teaching in light of some variables. The researcher adopted the descriptive survey method; a stratified random sample from the study population was selected, consisting of 255 male and female teachers. A 30-item scale was developed, and its psychometric properties were verified. The results showed that the general arithmetic mean of the study sample’s estimates regarding teachers’ attitudes toward the use of electronic games in teaching) 3.73(with a standard deviation of (0.489) indicating a high level of estimation. The results also showed no statistically significant differences at the significance level (α ≤ 0.05) in the attitudes of Karak teachers towards the use of electronic educational games in teaching, attributed to variables: gender, specialization, and teaching experience, and their interactions. The research concluded that teachers’ attitudes towards using electronic games in teaching are positive and high. The researcher recommended Enhancing the the necessity of providing the required technological infrastructure in classes Karak Governorate schools. This includes implementing standardized training programs for all teachers on designing and using educational e-games to transform this into a skill and a practical application